PENERAPAN ASURANSI DALAM PERSPEKTIF HADITS - Helmy Syamsuri; Andi Darussalam; Tasmin Tangngareng (Jurnal Teknologi Pendidikan Madrasah, 2024)
ABSTRACT The application of insurance from a hadith perspective is an in-depth study of the relevance and validity of insurance practices in Islam, based on the teachings contained in the hadith, or the words and actions of the Prophet Muhammad SAW. This research pays attention to hadiths related to the concept of insurance. This research uses the library research method or literature review with data collection carried out in several stages, starting from collecting references to analyzing references that are relevant to this research. The data sources are obtained from literature reviews from books, journals, the internet and other media. The results of the analysis in this research show that it can provide a more comprehensive view regarding the validity and limits of the application of insurance in Islam, by considering the values ​​contained in the hadith of the Prophet Muhammad SAW.